Go plant a tree, have a child, write a book - Cruz, Oscar V. (Pasay City Paulines, 2013)
Bishop Oscar Cruz's thoughts on sayings.
Keywords: Children -- Religious aspects -- Christianity; Children (Christian theology).; Christian life -- 21st century